Power and Representation in The Jakarta Post’s Article on UGM Rape Case Settlement - Indah Utami Chaerunnisah (English Department - University of Sultan Ageng Tirtayasa, 2020)
In 2019, a rape case involving two students of UGM went viral. After being headlines in many news articles, the case was settled in February, and one of the newspapers which cover this news is The Jakarta Post who released an article entitled ‘UGM settles alleged sexual abuse case’. Through systemic functional grammar, this study attempts at analyzing the transitivity processes and participants in the article, and it aims at describing how it signifies the power relation and representation in the article. This is a qualitative study which applied critical discourse analysis, and the data used are sentences and clauses taken from the news article. To analyze the data, the researcher applied Halliday’s transitivity theory and Fairclough’s theory on power and representation. The results of the study reveal that there is an unequal representation in the article where it gives more opportunities for UGM to deliver their statement and argument since UGM holds more power than the other participants.